Removal of the ovaries suppresses ethanol drinking and promotes aversion-resistance in C57BL/6J female mice - Sneddon, Elizabeth A.; Masters, Brianna M.; Shi, Haifei; Radke, Anna K. (Psychopharmacology, 2023)
Rationale Female rodents consume more ethanol (EtOH) than males and exhibit greater aversion-resistant drinking in some paradigms. Ovarian hormones promote EtOH drinking but the contribution of ovarian hormones to aversion-resistant drinking has not been assessed. Objectives We aimed to investigate the role of ovarian hormones to aversion-resistant drinking in female mice in a drinking in the dark (DID) task. Methods Female C57BL/6 J mice first underwent an ovariectomy (OVX, n = 16) or sham (SHAM, n = 16) surgery. Four weeks following surgery, mice underwent a DID paradigm where they were given access to water and 15% EtOH 3 h into the dark cycle for up to 4 h across 15 drinking sessions. To assess frontloading behavior, bottles were weighed at 30 min, 2 h, and 4 h. Aversion-resistance was tested by adding escalating concentrations of quinine (0, 100, 250, and 500 µM) to the 15% EtOH bottle on sessions 16 – 19. Results Removal of the ovaries reduced EtOH consumption in OVX subjects. When assessing aversion-resistant EtOH drinking, mice with ovarian hormones (SHAM) reduced consumption of 250 and 500 µM quinine in EtOH, while OVX subjects exhibited aversion-resistance at all quinine concentrations. OVX mice had greater frontloading for quinine + EtOH at higher concentrations of quinine. Conclusions These results indicate that circulating ovarian hormones may be protective against the development of aversion-resistant EtOH drinking and call for further investigation of the role of ovarian hormones in models of addictive behavior.